The effect of cryopreservation media on the quality of β-thalassemia mouse spermatozoa - Buranaamnuay K. (2023)
Background: The mouse model of human diseases is commonly used for biomedical study, including β-thalassemia (β-thal), an inherited hemoglobin disorder. Maintaining the mice strain by natural mating systems is costly and seems impractical, especially during the COVID-19 pandemic. Sperm-freezing is a cost-effective solution for β-thal mouse colony management. Aim: To determine appropriate cryopreservation media for β-thal mouse spermatozoa to establish a β-thal mouse sperm bank. Methods: The epididymal spermatozoa of C57BL/6 wild-type (WT) and β-globin gene knockout thalassemia (BKO) mice were frozen in four freezing media: I) raffinose–skim milk–monothioglycerol (MTG), II) raffinose–skim milk– glutamine, III) raffinose–egg yolk–glycerol, and IV) egg yolk–TES–Tris. The sperm quality was assessed prior to and following freeze-thawing. Results: Compared with WT counterparts, the viable spermatozoa before freezing exhibiting elevated levels of oxidative stress were significantly greater in BKO (p = 0.01). After thawing, the membrane integrity of BKO spermatozoa preserved in I was significantly lower (p = 0.001). The sperm viability and membrane integrity of BKO males were also inferior when media III and IV were used (p = 0.008–0.027). The amount of oxidative stress in the spermatozoon of BKO mice was significantly greater when preserved in I, III, and IV (p = 0.002–0.044). Comparing freezing media, the motility and acrosome integrity of WT and BKO spermatozoa preserved in IV were significantly higher than those in other media (p < 0.001 to p = 0.01). Spermatozoa with the highest mitochondrial membrane potential were observed in I in both genotypes (p = 0.012 to p > 0.05). The viability, membrane integrity, and oxidative stress of post-thaw BKO spermatozoa did not significantly differ among freezing solutions. Conclusion: Irrespective of freezing media, spermatozoa of BKO males are rather more sensitive to cryopreservation than those of WT. Raffinose–skim milk–MTG/glutamine, raffinose–egg yolk–glycerol, and egg yolk–TES–Tris can all be used to preserve BKO mouse spermatozoa. However, with slightly better sperm characteristics, egg yolk–TES– Tris may be a diluent of choice for BKO mouse sperm cryopreservation. The addition of a reducing agent to thawing media is also strongly recommended to efficiently prevent oxidative stress and therefore improve frozen-thawed sperm survival.